2017
DOI: 10.5194/bg-14-389-2017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of canopy stomatal conductance, transpiration, and evaporation in a temperate deciduous forest, validated by carbonyl sulfide uptake

Abstract: Abstract. Stomatal conductance influences both photosynthesis and transpiration, thereby coupling the carbon and water cycles and affecting surface-atmosphere energy exchange. The environmental response of stomatal conductance has been measured mainly on the leaf scale, and theoretical canopy models are relied on to upscale stomatal conductance for application in terrestrial ecosystem models and climate prediction. Here we estimate stomatal conductance and associated transpiration in a temperate deciduous fore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
197
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(207 citation statements)
references
References 45 publications
8
197
2
Order By: Relevance
“…Besides uptake of COS by the soil and leaf stomatal diffusion there is no other process to our knowledge that would lead to uptake of COS in the ecosystem. This leads to the conclusion that the nighttime COS uptake is predominantly driven by vegetative uptake and supports the use of COS to estimate g sCOS (Wehr et al, 2017). Assuming that the soil is the only sink besides the vegetation, we can say that the nighttime vegetative uptake contributes to 17 % of the total daily COS uptake.…”
Section: Stomatal Control Of Nighttime F Cossupporting
confidence: 74%
See 2 more Smart Citations
“…Besides uptake of COS by the soil and leaf stomatal diffusion there is no other process to our knowledge that would lead to uptake of COS in the ecosystem. This leads to the conclusion that the nighttime COS uptake is predominantly driven by vegetative uptake and supports the use of COS to estimate g sCOS (Wehr et al, 2017). Assuming that the soil is the only sink besides the vegetation, we can say that the nighttime vegetative uptake contributes to 17 % of the total daily COS uptake.…”
Section: Stomatal Control Of Nighttime F Cossupporting
confidence: 74%
“…This means that vegetative uptake of COS can continue during the night if stomata are not completely closed . Caird et al (2007) showed that nighttime stomatal conductance exists in a wide variety of plant species and several studies report nighttime depletion of COS mole fractions (White et al, 2010;Belviso et al, 2013;Commane et al, 2013Commane et al, , 2015Berkelhammer et al, 2014;Maseyk et al, 2014;Wehr et al, 2017). The measurements presented in White et al (2010), Maseyk et al (2014), Berkelhammer et al (2014) and Wehr et al (2017) indicated that nighttime ecosystem COS fluxes were indeed dominated by the vegetation, and not by the soil.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To understand the relationship between daily integrated COS and CO 2 fluxes for regional flux inversion (e.g., Hilton et al, 2015), nighttime COS uptake needs to be constrained . Nighttime COS uptake has been found in a wheat field , a boreal pine forest (Kooijmans et al, 2017), and temperate forests (Berkelhammer et al, 2014;Commane et al, 2015;Wehr et al, 2017). However, most field studies based their findings upon indirect evidence of nighttime ecosystem COS uptake, with only one study reporting some direct leaf observations of nighttime uptake 30 (Berkelhammer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since ocean COS emissions are geographically separated from the terrestrial COS sinks (leaf and soil), and anthropogenic emissions are usually concentrated as point sources, the spatial separation of dominant COS sources and sinks enables us to constrain land COS fluxes, and hence photosynthetic carbon uptake, from atmospheric COS observations (Campbell et al, 2008;Berry et al, 2013;Hilton et al, 2015). However, for the use of COS as a photosynthetic tracer, soil COS flux, which is unrelated to photosynthesis, needs to be understood and separated from the ecosystem COS flux that is the sum of leaf and soil fluxes Commane et al, 2015;Wehr et al, 2017).…”
mentioning
confidence: 99%